The wounded heart : hope for adult victims of childhood sexual abuse - Allender, Dan B. (NavPress, 2008)
"Sexual abuse knows no religious or social boundaries. The Wounded Heart is an intensely personal and specific look at this form of abuse. Dr. Allender explores the secret lament of the soul damaged by sexual abuse and lays hold of the hope buried there by the One whose unstained image we all bear. Includes information about false memory issues." -- Publisher description.